Introduction of nucleic acid amplification technology for blood screening in Hungary. (19th February 2021) - Siposné Sohajda, Réka; Kokavecz, László; Baróti‐Tóth, Klára; Nagy, Sándor; Paholcsek, Melinda; Stágel, Anikó
Abstract : Background & Aims: With this study, we intended to report our experiences about introducing nucleic acid testing for blood donation screening for human immunodeficiency virus, hepatitis B and C in Hungary. This study summarizes the experiences of nucleic acid amplification technology (NAT) screening of the first 16 months. Methods: The study was conducted from 5 June 2018 to 30 September 2019 in two phases. During the first 7 months of the study, the NAT tests were performed in parallel with serology. The yields of the methods were compared. After the initial seven months, only seronegative samples were tested by NAT. NAT tests were performed in minipools of 96. Results: In this 16‐month period, nearly 400 000 donations were screened by NAT. During the first phase, almost 150 000 samples were tested in parallel by serology and NAT screening. NAT screening during Phase I failed to identify 4 HCV‐ and 1 HBV‐reactive donations. In the second phase, about 245 000 seronegative samples were screened, with only one HBV reactive yield. Conclusions: Nucleic acid amplification technology testing proven to be an optimal diagnostic adjunct to serological screening, since it can help to identify early window period infections and occult hepatitis B infections. According to our experience however, the used pooling strategy represents a dilution rate of nucleic acid targets, which makes identifying these types of infections difficult. According to our cost–benefit analysis, reducing the pool size to 60 would result in a 60% sensitivity increase, at the expense of increasing the daily costs by 25%.